El sobrepeso y su influencia en la aparición de dislipidemia en la población de 20-49 años del subcentro las Malvinas del cantón ventanas durante el primer semestre del 2018 - Chevez Garcia, Carmen (2018)
Overweight is the accumulation of fat in the body, and most of it accumulates in the abdomen, having a sedentary lifestyle or bad eating habits, not having a balanced diet. Dyslipidemia is a disease that reflects excessive levels of total cholesterol, triglycerides, HDL (good cholesterol) and LDL (bad cholesterol) in the blood. The population studied was obtained through probabilistic sampling which results in a number of 41 patients from the Las Malvinas subcenter who had a BMI higher than 25 and their cholesterol levels were above the normal value and subsequently there was a presence of dyslipidemia. In the study methodology, the inductive method was applied with the modality of quantitative research, type of descriptive and field research, plus the use of the survey technique. The results were obtained through the surveys and with the help of the Excel 2013 tool, the results that lead us to the following conclusions: it was found that in overweight people can acquire dyslipidemia due to poor diet imbalance, in the Surveys were obtained by 34% for consuming foods with high caloric content, 17% physical inactivity, and 22% because they do not know foods with high caloric content.